Hubungan Jenis dan Frekuensi Makan serta Kecukupan Energi dengan Kejadian Gizi Lebih pada Mahasiswi Penikmat Drama Korea (Studi pada Mahasiswi S1 Gizi Fakultas Kesehatan Masyarakat Universitas Airlangga) - Ayuningtyas, Septiadeti Hidayati; Wirjatmadi, Bambang (Universitas Airlangga, 2024)
Background: Watching activity is one of the monotonous activities that is included in a form of sedentary lifestyle. Irregular eating patterns can be in the form of eating schedules that are not in accordance with the time and large portions of food have a role in increasing the risk of obesity. Objectives: The purpose of this study was to see the relationship between the type and frequency of eating as well as energy adequacy with the incidence of excess nutrition in female Korean drama connoisseurs in the Undergraduate Program of Nutrition, Universitas Airlangga. Methods: The type of research used in this study was analytic observational with a case-control study design with excess nutrition as the dependent variable and type, frequency, and energy adequacy as independent variables. The number of samples used in this study were 64 female students, namely 32 female students for the case group and 32 female students for the control group. In this study, the data collected was primary data which included data on the respondents' age, weight, height, and food consumption patterns. Results: The results of this study indicate that there is a relationship between energy adequacy and the incidence of overweight in women who enjoy Korean dramas in the Undergraduate Program of Nutrition. Meanwhile, the variables of type and frequency of eating have no relationship with the incidence of obesity in female Korean drama connoisseurs in the Undergraduate Program of Nutrition. Conclusions: The conclusion of this study is that most of the respondents who are overweight are included in the normal energy adequacy category and most of the others are included in the excess energy adequacy category. Therefore, it is expected that respondents can participate in regular nutritional status control activities so that the nutritional status of respondents/students is more controlled.